Maternal AP determinants in the Drosophila oocyte and embryo. (2nd June 2016) - Ma, Jun; He, Feng; Xie, Gengqiang; Deng, Wu‐Min
Abstract : An animal embryo cannot initiate its journey of forming a new life on its own. It must rely on maternally provided resources and inputs to kick‐start its developmental process. In Drosophila, the initial polarities of the embryo along both the anterior–posterior (AP) and dorsal–ventral (DV) axes are also specified by maternal determinants. Over the past several decades, genetic and molecular studies have identified and characterized such determinants, as well as the zygotic genetic regulatory networks that control patterning in the early embryo. Extensive studies of oogenesis have also led to a detailed knowledge of the cellular and molecular interactions that control the formation of a mature egg. Despite these efforts, oogenesis and embryogenesis have been studied largely as separate problems, except for qualitative aspects with regard to maternal regulation of the asymmetric localization of maternal determinants. Can oogenesis and embryogenesis be viewed from a unified perspective at a quantitative level, and can that improve our understanding of how robust embryonic patterning is achieved? Here, we discuss the basic knowledge of the regulatory mechanisms controlling oogenesis and embryonic patterning along the AP axis. We explore properties of the maternal Bicoid gradient in relation to embryo size in search for a unified framework for robust AP patterning. WIREs Dev Biol 2016, 5:562–581. doi: 10.1002/wdev.235 This article is categorized under: Establishment of Spatial and Temporal Patterns > Regulation of Size, Proportion, and Timing Gene Expression and Transcriptional Hierarchies > Quantitative Methods and Models Early Embryonic Development > Development to the Basic Body Plan